Construction of adjusting coefficients for sewing time of GSD system for knit products in Vietnam - Thanh Thao, Phan; Phan, Duy-Nam; Thu Uyen, Nguy Thi (International Journal of Psychosocial Rehabilitation, 2021)
The article presents the results of determining the adjustment coefficient between the actual values and theoretically calculated values according to both the MTM method and GSD predetermined time standard system of sewing time on the machine, and preparation time when sewing Polo-Shirt and T-Shirt from Single Jersey fabric. The study was conducted at Fashion Star Limited Company (Ha Noi) and Hanosimex Single Share-Holder Limited Company (Ha Nam). The simultaneous influence of stitch length (cm) and stitch density (stitch/cm) on sewing time was studied for the Polo-Shirt and T-Shirt products. The research was done on 4 kinds of machine, including single needle lockstitch machine, overlocking machine (1 needle and 3 threads), sewing machine (2 needles and 4 threads), and hemming machine (2 needles and 3 threads); and 3 kinds of single jersey fabrics, which are thin, medium, and thick fabrics. Besides, simultaneous influences of two factors, the size of the shirt and distance of semi-finished products (cm) to the sewing machines, on the sewing time were investigated. Experiment results were analzyed and processed using Design Expert 11.0. The results were used to construct the experimental regression equations, which showed correlations between the research factors,which are sizes and distances, and sewing time or preparation time. The optimal values of sizes and distances were determined to achieve the goal of minimizing preparation time. The adjustment coefficients between the theoretical calculation according to both MTM method and the GSD system and the practical results were identified. In addition, the formulae to calculate sewing time based on stitch density and stitch length values for 4 types of sewing machines and single jersey fabric with 3 thickness were built using orthogonal experimental planning method and multivariate optimization.